Risk factors for the recurrence of pelvic organ prolapse: a meta-analysis - Wei Shi; Lingling Guo (Taylor & Francis Group, 2023)
Female pelvic organ prolapse (POP) is a common condition, which has a high recurrence rate after reconstructive surgery, and the risk factors for POP recurrence are unclear. The aim of this study was to perform a meta-analysis to determine risk factors for POP recurrence. A thorough search of PubMed, Medline, EMBASE, Cochrane Central Register of Controlled Trials, and China Academic Journal Network Publishing Database was conducted for relevant publications until 29 October 2022, without language restrictions. A total of 29 studies involving 6597 patients were included, and the recurrence rate of POP after surgery was 37.7%. Significant OR and CI were found for levator avulsion (OR: 2.46, 95% CI: 1.80-3.36), preoperative stage ≥ III (OR: 1.87, 95% CI: 1.53-2.27), hiatal area on Valsalva manoeuvre (OR: 1.08, 95% CI: 1.03-1.12) and previous pelvic floor surgery (OR: 1.60, 95% CI: 1.07-2.39). Levator avulsion, preoperative stage ≥ III, hiatal area on Valsalva manoeuvre and previous pelvic floor surgery are significant risk factors for POP recurrence.IMPACT STATEMENT What is already known on this subject? It has been reported that genetic factors, parity, obesity, birth-induced injury during delivery, etc. are risk factors for POP development and recurrence after operation. What do the results of this study add? There are few literatures about the risk factors of POP recurrence at present. Our research has increased the information regarding risk factors for POP recurrence. What are the implications of these findings for clinical practice and/or further research? Our study provides an overview of the risk factors affecting POP recurrence and their contribution (OR, CI) to POP recurrence, which provides valuable evidence-based basis for clinical decision-making in POP treatment and prevention of POP recurrence.